BIODEGRADABLE SMART PACKAGING MATERIALS IN HALAL FOOD LOGISTICS: A REVIEW OF ENGINEERING INNOVATIONS - Suhartin Dewi Astuti; Ava Lee; Marcus Tan (Journal of Moeslim Research Technik, 2025)
The integrity of the halal food supply chain is paramount, yet it faces significant challenges from potential cross-contamination and environmental concerns associated with conventional packaging. This review examines the critical engineering innovations at this intersection, focusing on materials and systems that ensure both halal compliance and ecological responsibility. The objective is to identify key technologies, assess their compatibility with halal principles, and highlight their potential to improve supply chain integrity and sustainability. A systematic literature review was conducted using major scientific databases, including Scopus, Web of Science, and Google Scholar. The selected literature was analyzed to identify material compositions, sensor mechanisms, and their functional applications in maintaining halal integrity. The review identifies several promising innovations, including the development of biopolymer-based films (e.g., PLA, starch, chitosan) integrated with pH-sensitive and microbial spoilage indicators. These smart systems can provide real-time monitoring of food freshness and detect potential non-halal contaminants, such as ethanol or porcine derivatives, without direct contact. The findings show a strong trend towards non-invasive sensor technologies that align with the principles of tayyib (wholesome and pure). Engineering innovations in biodegradable smart packaging offer a robust solution for enhancing the security and sustainability of halal food logistics.